MANAJEMEN STRATEGI KEPALA MADRASAH DALAM OPTIMALISASI PRESTASI BELAJAR SISWA - Nuur Azizah; Achmad Ridlowi (Program Studi Manajemen Pendidikan Islam, 2023)
This research aims to analyze the strategies implemented by madrasa heads in improving student learning achievement. This research uses a qualitative method with a case study approach. Data was collected through observation, interviews and documentation analysis. The research results show that madrasa heads implement strategic management which includes three main stages: planning, implementation and evaluation. In this process, an analysis of students’ interests, talents and preferred subjects is carried out, which is then followed up with an appropriate coaching program. Periodic evaluations are also carried out to measure the effectiveness of the program and adjust strategies as needed. Supporting and inhibiting factors in optimizing student learning achievement are internal factors (interests, talents, motivation, health, cognitive abilities), while external factors (family, community, and school)